1993
DOI: 10.1002/hep.1840180530
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-associated C-reactive protein on rat liver macrophages is synthesized within the macrophages, expressed as Neo–C-reactive protein and bound through a C-reactive protein-specific membrane receptor

Abstract: We could recently show that rat liver macrophages (Kupffer cells) express a membrane-bound form of C-reactive protein on their surface. Because it is removed by washing the cells in buffers containing Ca(++)-chelators, membrane-bound C-reactive protein is a peripheral protein rather than an integral part of the Kupffer cell membrane. This Kupffer cell membrane-bound C-reactive protein is identical to the galactose-specific particle receptor previously characterized. We now present evidence that Kupffer cells d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In view of previous reports on a membrane-bound form of CRP being expressed by subsets of macrophages in human and rat (13, 37, 38), we first assessed the influence of hCRP transgenic hemopoietic cells on the development of Dep cells. When lethally irradiated B6 mice were reconstituted with bone marrow cells from Dep × hCRP mice, thereby generating animals in which only hemopoietic cells carried the hCRP transgene, no deletion of the Dep TCR was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of previous reports on a membrane-bound form of CRP being expressed by subsets of macrophages in human and rat (13, 37, 38), we first assessed the influence of hCRP transgenic hemopoietic cells on the development of Dep cells. When lethally irradiated B6 mice were reconstituted with bone marrow cells from Dep × hCRP mice, thereby generating animals in which only hemopoietic cells carried the hCRP transgene, no deletion of the Dep TCR was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Several particular features would predict strong immunogenicity of APPs upon induction: ( a ) the presence of very high serum levels (up to 2 mg/ml); ( b ) as part of the innate immune response, APPs accumulate at the site of infection and antigen processing; and ( c ) the uptake of APPs by professional APCs may be facilitated by specific surface receptors (12, 13). How is tolerance maintained under such conditions?…”
mentioning
confidence: 99%
“…CRP is synthesized mainly by hepatocytes. 12 , 13 Production of CRP by hepatocytes is induced mainly by IL-6, although other cytokines, such as tumor necrosis factor α (TNFα), transforming growth factor β (TGFβ), and IL-1, can also synthesize this protein. 35 , 36 It has been reported that IL-6 is able to contribute to the cancer growth and progression.…”
Section: Discussionmentioning
confidence: 99%
“… 9 11 CRP is synthesized mainly by hepatocytes as a part of the SIR. 12 , 13 CRP is a representative acute-phase reactant and is the most widely used systemic biomarker of inflammation. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence indicates extrahepatic synthesis of CRP. CRP messenger RNA and/or protein were detected in monocytedepleted peripheral-blood lymphocytes, 58,59 peripheral-blood mononuclear cells, 60 rat Kupffer cells, 61 macrophages, 13,62 islet cells of the pancreas, 63 neurons, 64 adipose tissue, 65 endothelial and smooth muscle cells, 17,18 kidneys, 66 and epithelial cells of the respiratory tract. 14 Most of the described CRP proteins synthesized extrahepatically express poor solubility (ie, the protein is not secreted, is either expressed intracellularly or bound to the cell membrane) and express mCRP ("neo-CRP") antigenicity.…”
Section: Immunohistochemistrymentioning
confidence: 99%